An Analysis of Using Code-Mixing on Podcast "Guruku Mr. D" Youtube Channel - Febriyantina Istiara; Tommy Hastomo; M.Havid Febriansyah; Daning Larasati (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2022)
This study examines the code-mixing in a podcast from Mr. D's YouTube channel. It was chosen because code-mixing is very important for everyone, especially for people who live in a multilingual society. Sometimes they need multiple languages to talk to other people around them. Some of them replace or mix their mother tongue with their foreign or second language. This phenomenon occurs on the Podcast on Mr. D's Youtube channel. Qualitative methods are used to describe and explain the phenomenon of code-mixing in Mr. D's Podcast. The researcher is primarily an instrument for collecting and analyzing data. The results showed that the types of code-mixing are classified as intra sentential code-mixing, inter lexical code-mixing, and involving a change in pronunciation. The levels of code-mixing are classified as word level, phrase, baster, repetition, idiom, and clause level. Using code-mixing is to look more prestigious and make it easier for the speaker when it is difficult to find words in other languages. Finally, the affective functions of code-mixing are serving quotes, marking personalization and objectification, qualifying and clarifying messages, and determining recipients.